177k views
2 votes
Solve the equation 3(y-9)=7y+2

User Leymannx
by
5.7k points

2 Answers

1 vote
First, distribute.

3y - 27 = 7y + 2
Subtract the 3y from both sides.

- 27 = 4y + 2
Subtract 2 from both sides.

- 29 = 4y
To get the variable by itself, divide by 4.

- (29)/(4) = y
Your answer is:

y = - (29)/(4)
User Nijel
by
7.2k points
3 votes

Explanation:

I'm really really sorry if I'm wrong...

3(y-9)=5y+2

3y - 27 = 5y + 2

+ 27 + 27

3y = 5y + 29

-5y -5y

-2y = 29

-2 -2

y = -14.5


User Asyraf Arifin
by
5.7k points